Plantes antilithiasiques utilisées en médecine traditionnelle dans la ville d’Oran, Algérie - Walid Khitri; Nassima Lachgueur; Abdessamed Tasfaout; Abderrahmene Lardjam; Ali Khalfa (Revue d'ethnoécologie)
An ethnobotanical survey of the herbalists' and traditional healers' work was carried out in Oran (Algeria) during a period of two months (January and February 2014). 35 plants used in the traditional treatment of urolithiasis were inventoried. The most recommended plant has been selected for phytochemical screening.